Inflammatory arthritis and eye diseases: a Mendelian randomization study - Nie, Xinlin; Liu, Zhaoliang; Xie, Dongheng; Sun, Yang (Frontiers in Endocrinology, 2023)
To determine causal associations between inflammatory arthritis and eye diseases (Disorders of sclera, cornea, iris and ciliary body [DSCIC]; Disorders of choroid and retina [DCR]).Genome-wide association studies summary data of rheumatoid arthritis (RA) from a Large-scale meta-analysis were used to identify genetically predicted RA. UK Biobank source data predicted ankylosing spondylitis (AS), psoriatic arthritis (PsA) and juvenile idiopathic arthritis (JIA), respectively. Further, data from the FinnGen Biobank were used to identify genetically predicted eye diseases. Two-sample Mendelian randomization analysis was used to assess the causal relationship between inflammatory arthritis and eye diseases in European. Inverse-variance weighted (IVW) was used as the primary method, while MR-Egger, weighted median, and MR-PRESSO outlier test were used to detect heterogeneity and pleiotropy.Genetically determined RA was indeed observed to have a causal effect on DSCIC (odds ratio [OR]=1.084, P=2.353×10 -10 ) and DCR (OR=1.151, P=1.584×10 -19 ). AS was causally associated with DSCIC (OR=1.068, P＜2.024×10 -8 ). In addition, PsA was also found to have a causal association with an increased risk of 17.9% for the development of DSCIC (OR=1.179, P=0.003). On the flip side, DSCIC increased the risk of JIA (OR=2.276, P=0.003).Our study provided genetic evidence for the causal associations of RA, AS, and PsA with an increased risk of DSCIC, a causal association between RA and DCR was also identified. In addition, DSCIC greatly increased the risk of JIA.